Konsep Penataan Lanskap di Area Air Terjun Uma Anyar Desa Kemenuh Kabupaten Gianyar - Agus Darmayoga, I Kadek; Arya Dimas Suputra, Kadek; Sherlystia Satriani, Ni Putu; Dwi Utari, Ni Made (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Uma Anyar Waterfall is one of the potential objects to be developed into a tourist attraction in Kemenuh Village, Sukawati District, Gianyar Regency. However, the main challenge faced is the lack of tourist support facilities such as parking areas, changing rooms, and adequate vegetation, which can affect visitor comfort and the visual appeal of the area. Therefore, the Udayana University KKN-T Team conducted community service in Kemenuh Village in the form of making a concept of landscape arrangement in the Uma Anyar Waterfall area to be developed into a better tourist attraction in the future. Concept design is carried out based on solving problems with the object using data sources obtained through field observations and interviews with related parties. The structuring concepts to be designed include the arrangement of parking areas, entrance areas, landscaping, and vegetation, as well as changing rooms, gazebos, and relaxing regions as supporting facilities. Each arrangement concept is discussed with partners so that the design results are representative of the community's expectations. The final designs, in 2D and 3D, will be finalized and submitted to Kemenuh Village for implementation as part of long-term tourism development.